Analysis of business strategies in the context of post-pandemic COVID-19 (Research, Society and Development, 2021)
Some companies around the world routinely apply development measures in business strategies. The COVID-19 pandemic, caused by the new corona virus, in addition to causing loss of life, directly affected the world economy and forced companies to adapt to this pandemic context. Given this issue, the general objective of this work was to identify which business strategies local, regional and international companies have applied to adapt in the context of the COVID-19 pandemic in the world. This article opted for a qualitative methodology, bibliographical research was used to better address the problems faced by corporations, identifying procedures to have resilience in the face of this new reality. As a result, companies started to seek help from banks through new lines of credit offered by governments, adapting to decrees in new working hours and working alternatives that allowed temporary leave, reduced work and salary, and paid layoffs from rescissions in installments, or collective vacations, to make adjustments in the hygienic and sanitary conditions so that they could proceed with the service to the public and increase their investments in digital media. The study concluded that some segments, using a lot of efforts, showed growth, bringing some stability to the economy and driving the adoption of new economic strategies. On the other hand, there are still delicate situations that deserve a closer look at the level of unemployment and the fight against poverty, which are still at very high levels.